Deslintamento químico: efeitos sobre a qualidade de sementes de algodão - Vaz-Tostes, Douglas Pelegrini (2021)
Cotton cultivation has great socioeconomic importance in Brazil, and is the main natural source of fibers, which guarantees the country a privileged place in the world scenario, as one of the five largest producers. The highlight of Brazilian cotton farming, among other aspects, is associated with investments made in crop management technologies, pest and disease control, use of biotechnology and, above all, the use of high quality seeds. The first post-harvest process to obtain cotton seeds is ginning, however, after this step, the seed retains a covering of short fibers adhered to its integument, called linter. Cotton seed delinting consists of removing short, dense fibers that are arranged around the seed, and is of fundamental importance to increase water absorption, facilitate seed handling in seeders, contribute to efficient storage, facilitate improvement and emergence in the field. The work was divided into three chapters. The first aimed to verify the potential use of computerized image analysis in the evaluation of delinting and possible damage to the seed coat of cotton. In the second, to evaluate the neutralization process of concentrated sulfuric acid in seeds and the residue generated after delinting with different basic compounds. And finally, in the third, to evaluate the quality of cotton seeds after the delinting and neutralization process, in order to generate concise data regarding sulfuric acid dosages, turning and neutralization times, used in delinting. Computerized image analysis is efficient in the evaluation of cotton seeds as it is able to distinguish different levels of delinting and surface damage to the integument. The basic solutions of NaOH, Na2CO3 and Ca(OH)2 are efficient for the neutralization in the chemical delinting process and do not interfere negatively in the quality of cotton seeds. The calcium hydroxide solution [7.2% (m/V)] is the most efficient for neutralization in the chemical delinting process, as it results in a more basic pH of the seed exudate and residual liquid, when compared to other compounds basic. The quality of cotton seeds is positively influenced by the chemical delinting process, in the dosage of 70 mL of sulfuric acid and turning time of 21 minutes, and neutralization after delinting with a solution of calcium hydroxide [Ca(OH)2] a 7.2% + washing with water.